Parkinsonism driven by antipsychotics originates from dopaminergic control of striatal cholinergic interneurons - Kharkwal, Geetika (Neuron, 2016)
Typical antipsychotics can cause disabling side effects. Specifically, antagonism of D2R signaling by the typical antipsychotic haloperidol induces parkinsonism in humans and catalepsy in rodents. Striatal dopamine D2 receptors (D2R) are major regulators of motor activity through their signaling on striatal projection neurons and interneurons. We show that D2R signaling on cholinergic interneurons contributes to an in vitro pause in firing of these otherwise tonically active neurons and to the striatal dopamine/acetylcholine balance. The selective ablation of D2R from cholinergic neurons allows discrimination between the motor-reducing and cataleptic effects of antipsychotics. The cataleptic effect of antipsychotics is triggered by blockade of D2R on cholinergic interneurons and the consequent increase of acetylcholine signaling on striatal projection neurons. These studies illuminate the critical role of D2R-mediated signaling in regulating the activity of striatal cholinergic interneurons and the mechanisms of typical antipsychotic side effects.